C11 Generation of isogenic HD-IPSCS to investigate genetic modifiers of huntington's disease. (September 2018) - Donaldson, Jasmine; Massey, Thomas; McAllister, Branduff; Allen, Nicholas; Jones, Lesley
Abstract : Background: Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder caused by the expansion of a CAG repeat in the huntingtin gene, HTT. The length of the CAG repeat is inversely correlated with age at motor onset but other factors influence onset including genetic variation elsewhere in the genome. Recent genome-wide association studies (GWAS) have identified genetic variants in or near DNA repair genes as modifiers of age at onset. We hypothesise that DNA repair processes trigger post-mitotic CAG repeat expansion in medium spiny neurons (MSNs), the cells most susceptible to the disease, leading to their degeneration. Evidence from post-mortem human HD brains and HD mouse models suggests that CAG expansion in neurons may drive HD pathogenesis, but thus far has been difficult to study in vitro . Induced pluripotent stem cells (iPSCs) derived from patients with HD provide a unique opportunity for modelling HD pathogenesis. Methods and Results: HD-iPSC lines with expanded CAG repeat tracts of >100 CAG show repeat instability in culture, with the repeat tract undergoing further expansions in pluripotent cells and upon neuronal differentiation. Using these cell lines as models of CAG repeat expansion we can characterise how genetic variants in DNA repair genes affect cells harbouring expanded CAG repeats. To study the precise contribution of specific genetic factors to disease processes we report the generation of isogenic pairs of iPSCs, that differ only in the length of the CAG repeat. Employing CRISPR-Cas9 and a piggyBac transposon-based homologous recombination approach we show the seamless correction of the HD-iPSC lines with a CAG repeat length of 109 to a 'wild-type' repeat length of 22 CAG. Corrected HD-iPSCs maintain a normal karyotype and pluripotency, demonstrated by a SNP array and immunohistochemistry. Corrected clones were further able to differentiate towards neurons expressing DARPP-32 and CTIP2, indicative of MSNs. Conclusions: We anticipate that correction of the disease-causing mutation will rescue the disease-like phenotypes previously reported and our isogenic stem cell model will thus provide a valuable platform to elucidate the role of DNA repair in HD pathogenesis.